Elemental composition of Eucheuma cottonii and Gracillaria sp. using scanning electron microscope-energy dispersive spectroscopic analysis. Issue 1 (April 2021) - Agusman; Wibowo, S
Abstract: Indonesia is a major producer of the E. cottonii seaweed and Gracillaria sp. in the world. The farmers usually dry that seaweeds before sending them to plant factories to be processed into carrageenan or agar. In the present work, E. cottonii and Gracillaria sp. seaweed's chemical composition were observed using Scanning Electron Microscope-Energy Dispersive Spectroscopic (SEM-EDS) analysis, and the distribution of the main salt-minerals in the surface and the cross-section thallus of both samples were conducted. The results showed that the surface of E. cottonii contains the following order of elements Cl> K> Na> S> Ca> C> O> Si> Al> Mg> Fe> Mn> Zn and in the cross-section contains order of elements S> Cl> K> C > O> Na> Mg> Ca> Al> Zn> Fe> Si> Mn. Whereas on the surface of the Gracillaria sp. showed the presence of elements in the following order Cl> K> Si> C> O> Al> S> Fe> C> Mg> Na> Mn> Zn and on the cross-section found elements in the following order Cl> K> C> O> S> Na> Si> Al> Mg> Fe> Ca> Zn> Mn. The EDS mapping on both seaweeds surface and cross-section showed a random distribution of salt-forming elements Na, K and Mg. Furthermore, the presence of a higher amount of K, Na, adequate amount Mg, and other essential elements indicated both seaweeds' potential to be developed for salts with special functional properties.